Global trends in the research on benign paroxysmal positional vertigo: A 20-year bibliometric and visualization analysis - Zhou, Fangwei; Yu, Bingxi; Luo, Jiali; Ma, Yifei; Li, Jianyao; Zhang, Tian; Yu, Guodong (Frontiers in Neurology, 2022)
Background Benign paroxysmal positional vertigo (BPPV) is the most common cause of peripheral vestibular vertigo. Although BPPV is benign, its underlying mechanisms are complicated, and patients diagnosed with BPPV are significantly affected by it in their daily lives. Hence, this study's purpose was to investigate global trends and frontiers in the field of BPPV. Methods We searched the research literature published from 2002 to 2021 on BPPV using two databases from the Web of Science Core Collection, and we conducted a bibliometric and visualization analysis. Bibliometric tools were used to perform co-authorship, co-citation, and co-occurrence analyses of countries or regions, institutions, authors, journals, keywords, and references. Results In all, 1,419 publications from 4,594 authors, 1,542 institutions, and 65 countries or regions with 71 subject categories were included in the study. The number of articles increased gradually from 2002 to 2021. Seoul National University, the University of Munich, and Osaka University were among the leading institutions with the most publications, while United States of America, South Korea, and China were the leading countries. JS Kim was the most prolific author, Otology & Neurotology was the most prolific journal, and Otorhinolaryngology was the most published subject category. The five most frequently occurring keywords were BPPV, vertigo, dizziness, nystagmus, and management and the top research hot spots were osteoporosis and vitamin D. Conclusion This study systematically analyzed trends in global scientific research on BPPV. The academic understanding of BPPV has improved significantly over the last two decades, with osteoporosis and vitamin D the two main research hot spots in the field of BPPV in recent years. These findings provide direction for current research to grasp the trends and research frontiers of current research.